SHORT DIALOGUES MEMORIZATION TO IMPROVE STUDENTS’ SPEAKING ABILITY - Sudarsono Sudarsono; Regina Regina; Atrianus Toni (STKIP Persada Khatulistiwa Sintang, 2021)
This research aimed at improving students’ speaking ability using a short dialogue memorization technique. It was a classroom action research. The study was conducted in a cyclic process, starting from planning, acting, observing, and reflecting. It was implemented in two cycles. The subjects of this research were the elementary level students from Timothy English School, Sintang. The study found out that the implementation of the short dialogue memorization technique has improved the active involvement of the students in class. The students also improved their speaking ability well. In the first cycle, only some students participated in class actively, and most of them were very active in the second cycle. Referring to the data, more than half of the students got higher score in each aspect. Compared with Cycle 1, Cycle 2 was dominated by the students who got a score of 3 in each aspect, while Cycle 1 was dominated by the students who got score 2 and 1. Almost all students passed the criteria of success, 65. Therefore, the teachers were recommended to improve the students’ speaking ability using short dialogue memorization technique.